Analisis Framing Pada Pemberitaan Putusan Mahkamah Agung (MA) Nomor 23 P/Hum/2024 Tentang Batas Usia Calon Kepala Daerah Di Media Online Detik.Com - Maryadi, Nurul Lutfia; Irawansyah, Azahra Kaulika; Putri, Chika Syaharani; Saputra, Haris Rizki (Universitas Majalengka, 2024)
This article aims to analyze the framing of news coverage concerning the Supreme Court (MA) Decision No. 23 P/HUM/2024 in the online media Detik.com. The research employs framing analysis methodology to understand how Detik.com frames this news. This method involves literature review and secondary data collection from articles published by Detik.com, chosen for its significant influence on shaping public opinion as a leading news portal in Indonesia. The framing analysis focuses on examining elements such as headlines, news content, quotes, and sources, as well as the background and chronology of events. The primary focus is to explore how the news about MA Decision No. 23 P/HUM/2024 is constructed through word choice, use of quotes, and emphasis on specific aspects of the case. This research also aims to identify any bias or tendencies in the reporting and assess its impact on public perception. The findings are expected to provide in-depth insights into the media's role in reporting significant legal decisions and their implications for information transparency and democracy.